2020
DOI: 10.1002/adfm.201909707
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Biodegradable Organic Transistors Using a Solid‐State Electrolyte Incorporated with Choline‐Based Ionic Liquid and Polysaccharide

Abstract: Biocompatible, biodegradable, and solid‐state electrolyte‐based organic transistors are demonstrated. As the electrolyte is composed of all edible materials, which are levan polysaccharide and choline‐based ionic liquid, the organic transistor fabricated on the electrolyte can be biocompatible and biodegrable. Compared to the other ion gel based electrolytes, it has superior electrical and mechanical properties, large specific capacitance (≈40 µF cm−2), non‐volatility, flexibility, and high transparency. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 85 publications
0
94
0
1
Order By: Relevance
“…The drawback of this approach was that the semiconducting material, PTCDI-C8, was not degradable. This was also the case for the work of Jo et al who reported a biodegradable organic transistor using a solid-state biodegradable electrolyte [ 129 ], more precisely based on a levan polysaccharide and a choline-based ionic liquid. The electrolyte presented a specific capacitance of 40 µF·cm −2 and the transistor showed low operating voltage.…”
Section: Discussionmentioning
confidence: 61%
“…The drawback of this approach was that the semiconducting material, PTCDI-C8, was not degradable. This was also the case for the work of Jo et al who reported a biodegradable organic transistor using a solid-state biodegradable electrolyte [ 129 ], more precisely based on a levan polysaccharide and a choline-based ionic liquid. The electrolyte presented a specific capacitance of 40 µF·cm −2 and the transistor showed low operating voltage.…”
Section: Discussionmentioning
confidence: 61%
“…However, the need for higher functions, such as sensing or monitoring for proper treatment, has led to advances in bioresorbable electronics. Various types of bioresorbable devices, such as sensors, [16,[78][79][80][81] batteries, [82][83][84] transistors, [85,86] and capacitors, [87][88][89] have been developed, and bioresorbable integrated systems [90][91][92] were produced using each electronic component. Bioresorbable integrated systems offer a controllable feedback loop, enabling both monitoring and treatment.…”
Section: Bioresorbable E-drugs For Monitoring and Treating Short-term Diseasesmentioning
confidence: 99%
“…For ECG monitoring, Jo et al proposed solid-state electrolyte-based bioresorbable organic transistors. [85] For the fabrication of the transistor, carboxyl-functionalized poly(3-hexylthiophene), poly [3-(5-carboxypentyl) thiophene-2,5-diyl] (P3CPT) was used as a p-type semiconducting polymer, while Cr and Au were deposited as an electrode component on the Levan-based solid-state electrolyte (LSE) substrate. The fabricated transistors showed water solubility, fully dissolving when immersed in deionized water for 120 min.…”
Section: Bioresorbable Sensors For Physical Condition Monitoringmentioning
confidence: 99%
“…对于p型材料, PEDOT体系是目前研究最为广泛 的有机热电材料. 2011年, Crispin课题组 [77] 报导了水 溶PEDOT:Tos材料体系, 通过调控体系的氧化掺杂程 图 7 (a) P3CPT与DPP-ran-Se/TVT的分子结构式; (b) TVT/Se比例对DPP类聚合物的双极性性能影响 [63] ; (c) 心电信号传感的 OTFT结构示意图; (d) OTFT传感器贴于人体脉搏的照片; (e) 受试者标准心电信号图; (f) OTFT传感的受试者心电信号图; (g) 器件贴于大鼠心脏上进行传感的照片; (h) 器件长时间传感大鼠心跳的心电信号图 [68] (网络版彩图) 表 2 可绿色溶剂加工的有机热电器件的性能指标 ) 除了上述材料, 人们不断尝试发展新的分子体系.…”
Section: 近十年 得益于乙烯四硫醇镍和Pedot体系的性unclassified